Usuń nawiasy i wykonaj redukcję wyrazów podobnych:
a) 4c- (3x+2)- 10c=
b) 7x-8-(5x+6)=
c) 9y -(8-3y) + 16=
d) 5x - (2-4x) + 8x - 7=
e) -(-5c-8)+6-9c-c=
f) -4(3x-6) - 3 (2+7x)=

Uprość wyrażenie:
a) 6 (a+2b)-3(2a-3b)
b) 4 (b+3) + 3 ( a-b)
c) 7(b+c)-3(b+2c)
d) 5(a+3) + 2b - 3 (a+b)
e) 6(3+z) - 4(2z+4)+ 2 (8+z)
f) -4(2x-7-3y) - 12 (-y-x)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-01T17:56:34+01:00
A) 4c-3x-2-10c= -6c-3x-2
b) 7x-8-5x-6= 2x-14
c) 9y-(8-3y)+16= 9y-8+3y+16= 12y-8
d) 5x-(2-4x)+8x-7 = 5x-2+4x+8x-7= 17x-9
e) -(-5c-8)+6-9c-c = 5c+8+6-9c-c= -5c+14
f) -4(3x-6)-3(2+7x)= -12x+24-6-21x= -33x+18


a) 6(a+2b)-3(2a-3b)= 6a+12b-6a+9b= 21b
b) 4(b+3)+3(a-b)= 4b+12+3a-3b= 1b+3a+12
c) 7(b+c)-3(b+2c)= 7b+7c-3b-6c= 4b+1c
d) 5(a+3)+2b-3(a+b)= 5a+15+2b-3a-3b= 2a-1b+15
e) 6(3+z)-4(2z+4)+2(8+z) = 18+6z-8z-16+16+2z= 18
f) -4(2x-7-3y)-12(-y-x)= -8x+28+12y+12y+12x= 4x+24y+28